2012
DOI: 10.5194/acp-12-169-2012
|View full text |Cite
|
Sign up to set email alerts
|

Attribution and evolution of ozone from Asian wild fires using satellite and aircraft measurements during the ARCTAS campaign

Abstract: Abstract.We use ozone and carbon monoxide measurements from the Tropospheric Emission Spectrometer (TES), model estimates of Ozone, CO, and ozone pre-cursors from the Real-time Air Quality Modeling System (RAQMS), and data from the NASA DC8 aircraft to characterize the source and dynamical evolution of ozone and CO in Asian wildfire plumes during the spring ARCTAS campaign 2008. On the 19 April, NASA DC8 O 3 and aerosol Differential Absorption Lidar (DIAL) observed two biomass burning plumes originating from N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 103 publications
1
22
0
Order By: Relevance
“…The use of the mean monthly 8-hr max O 3 concentration as an indicator was corroborated by previous evidence that wildfires contribute episodically to high O 3 concentrations at receptor sites several days or weeks following the fire (Jaffe et al, 2004;Junquera et al, 2004;Pfister et al, 2006). For example, Dupont et al (2012) recently reported that two wildfires events in Asia influenced O 3 levels in the US after 10-12 days. During the analysis, we identified cases in which fire detection was observed after the highest O 3 concentration.…”
Section: Ozone Data Acquisition and Reductionsupporting
confidence: 50%
“…The use of the mean monthly 8-hr max O 3 concentration as an indicator was corroborated by previous evidence that wildfires contribute episodically to high O 3 concentrations at receptor sites several days or weeks following the fire (Jaffe et al, 2004;Junquera et al, 2004;Pfister et al, 2006). For example, Dupont et al (2012) recently reported that two wildfires events in Asia influenced O 3 levels in the US after 10-12 days. During the analysis, we identified cases in which fire detection was observed after the highest O 3 concentration.…”
Section: Ozone Data Acquisition and Reductionsupporting
confidence: 50%
“…Dupont et al (2012) made the observation that, in addition to photochemical production of O 3 from precursors formed in the plumes, exchange between the stratosphere and the troposphere was a major factor influencing O 3 concentrations in plumes measured during ARCTAS. Biomass burning emissions can be injected into the upper troposphere by isolated convection that is not fire related as well as by pyroconvection; are fire-aided convective processes capable of perturbing the tropopause and permitting O 3 from stratospheric air into the free troposphere?…”
Section: Stratosphere-troposphere Exchange Due To Pyroconvective Updrmentioning
confidence: 99%
“…Various systems for the generation of up-to-date, or even NRT global fire emission estimates have been reported Wiedinmyer et al, 2010). Chemical composition in fire plumes is assessed using a range of satellite instruments as well as model results from various systems, some of them including chemical data assimilation (Verma et al, 2009;Dupont et al, 2012;Val Martin et al, 2006;Real et al, 2007). Uncertainties in fire inventories on the modeling of atmospheric composition, e.g., Williams et al (2012), and long-range transport (Miller et al, 2011;McMillan et al, 2010;Elguindi et al, 2010) have previously been quantified.…”
Section: Huijnen Et Al: Tropospheric Composition During 2010 Russmentioning
confidence: 99%